Understanding the acoustics of St. John's Baptistery in Pisa through a virtual approach. Issue 3 (3rd May 2020) - D'Orazio, D.; Fratoni, G.; Rossi, E.; Garai, M.
ABSTRACT: The virtual acoustics provide an important tool in the comprehension of the architectural evolution of a historical place, offering the possibility to consciously operate for its preservation. St. John's Baptistery represents an outstanding example of medieval architecture, recognized as UNESCO World Heritage and popular for its huge reverberation. When compared to other similar central-symmetry buildings, the Baptistery proves to be an outlier, enough to raise the interest of scholars. A model of the building was calibrated considering in situ acoustic measurements, the material properties and the liturgical use. The numerical simulations of the current geometry and the early design hypotheses are used to understand the factors affecting the peculiar sound behaviour. The temporal analysis of a Gregorian chant – ad hoc recorded – seems to confirm the needing of large reverberation.